2002
DOI: 10.1080/1361126022000002465
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring with Disaffected Pupils

Abstract: This article focuses on a critical evaluation of progress being made by a number of major innovative schemes which are aimed at raising standards in schools and combating disaffected behaviour. Prominent amongst these schemes are the new Connexions Service, Excellence in Cities and Education Action Zones as well as other major initiatives. This article is the rst to pull these strands together by examining their current approaches with disaffected pupils. It concludes by indicating that it is unlikely that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…In particular, a number of studies have highlighted the need for the adults involved in such programmes to possess characteristics that will facilitate positive relationships; e.g. credibility, fairness, consistency and respect (Riley & Rustique-Forrester, 2002;Wilson & White, 2001) and there is further evidence to support this claim in the literature on youth mentoring and informal education (Reid, 2002;Ellis, 2003;Richardson & Wolfe, 2001). …”
Section: The Impact Of Sport/physical Activity On Positive Youth Devementioning
confidence: 86%
“…In particular, a number of studies have highlighted the need for the adults involved in such programmes to possess characteristics that will facilitate positive relationships; e.g. credibility, fairness, consistency and respect (Riley & Rustique-Forrester, 2002;Wilson & White, 2001) and there is further evidence to support this claim in the literature on youth mentoring and informal education (Reid, 2002;Ellis, 2003;Richardson & Wolfe, 2001). …”
Section: The Impact Of Sport/physical Activity On Positive Youth Devementioning
confidence: 86%
“…The importance 650 of the role of an adult 'mentor' has been stressed in numerous contexts within the physical education, 651 informal education and mentoring literature (e.g. Martinek & Hellison, 1997;Richardson & Wolfe, 652 2001; Reid, 2002) and it has been suggested that having someone to turn to who is more than 'just' a 653 teacher is important for some young people (Bennetts, 2003;Vulliamy & Webb, 2003). In the 654 HSBC/OB programme, one of the key features was the training of adult mentors from within HSBC 655 staff to work with young people on programme activities.…”
Section: Discussion 608mentioning
confidence: 99%
“…There has also been a proliferation in the literature on mentoring, with authors highlighting a drive to encourage adults to take up mentoring roles with young people in a number of countries including North America, the UK, and Australia (Reid, 2002;Colley, 2003a;Philip et al, 2004;DuBois & Karcher, 2005). Tackling youth disaffection and social exclusion is a key target for many mentoring initiatives (Shiner, Newburn, Young & Groben, 2004) based on research which suggests that a learning relationship with an adult other than a parent (or teacher) can lead to positive outcomes for disaffected young people (Bennetts, 2003) and that these connections can "powerfully influence the course and quality of adolescents' lives" (Rhodes, 2001 p.1).…”
Section: An Overview Of Relevant Mentoring and Informal Education Litmentioning
confidence: 99%
“…Tackling youth disaffection and social exclusion is a key target for many mentoring initiatives (Shiner, Newburn, Young & Groben, 2004) based on research which suggests that a learning relationship with an adult other than a parent (or teacher) can lead to positive outcomes for disaffected young people (Bennetts, 2003) and that these connections can "powerfully influence the course and quality of adolescents' lives" (Rhodes, 2001 p.1). Reid (2002) sums up the suggested benefits of youth mentoring as follows:…”
Section: An Overview Of Relevant Mentoring and Informal Education Litmentioning
confidence: 99%